The peculiarities of the polyvinylpyrrolidone copolymers synthesis for contact lense - Suberlyak, Oleg; Skorokhoda, Volodymyr (Publishing House of Lviv Polytechnic National University, 2007)
Приведені результати досліджень закономірностей синтезу гідрогелів на основі кополімерів 2-гідроксіетилметакрилату з полівінілпіролідоном та ефективні шляхи регулювання їх властивостей. Синтезовані кополімери виявились ефективними матеріалами для виробництва гідрофільних контактних лінз. The research results of the hydrogels synthesis rules on the basis of 2-hydroxyethylmethacrylate- polyvinylpyrrolidone copolymers and effective ways of adjusting of their proper-ties are given. Synthesized copolymers appeared to be effective materials for production of hydrophilic contact lenses.
Особливості синтезу кополімерів полівінілпіролідону для контактних лінз
Keywords: гідрогель; полівінілпіролідон; 2-гідроксіетилметакрилат; контактні лінзи; hydrogel; polyvinylpyrrolidone; 2-hydro- xyethylmethacrylate; contact lens